A novel glucan from Sparassis latifolia: purification, structural characterization and protective effect on gastric mucosal cells against ethanol-induced damage - Mengyu Wang; Guoying Lv; Ruimeng Zhao; Weiming Cai; Zuofa Zhang (Chemical and Biological Technologies in Agriculture)
Abstract Sparassis latifolia is a rare edible mushroom with many pharmacological activities. Active screening found that the crude polysaccharide from this mushroom (SLP) exhibited noticeable gastroprotective effects. However, it remains unclear regarding the underlying regulatory mechanism of the gastroprotective effects of SLP. A novel polysaccharide SLP-2 was purified from the fruiting bodies of S. latifolia, and characterized using FT-IR, HPAEC, SEM, SEC–MALLS-RI, methylation, and NMR analysis. Structural characterization revealed that the backbone of SLP-2 was mainly composed of → 4)-α-D-Glcp-(1 → , → 3)-α-D-Glcp-(1 → and → 3,4)-α-D-Glcp-(1 → . The branched chain primarily consisted of β-D-Glcp-(1 → linked to the sugar residue → 3, 6)-β-D-Glcp-(1 → at the O-6 position and → 3,4)-β-D-Glcp-(1 → at the O-4 position. Physiological experimental results demonstrated that SLP-2 effectively protected GES-1 cells against ethanol-induced damage by suppressing intracellular ROS levels and cell apoptosis while elevating the activities of SOD and CAT enzymes. Furthermore, transcriptome analysis revealed molecular mechanisms underlying the gastroprotective effect of SLP-2, with KEGG enrichment suggesting associations with ferroptosis, TNF, PI3K–Akt, MAPK and IL-17 signaling pathways. These findings provide a technological foundation for valuable utilization of S. latifolia and emphasize the potential application of SLP-2 in repairing gastric mucosal injuries. Graphical Abstract